On certain subclasses of Meromorphically p-Valent functions associated by the linear operator Dn. - Saif, Amin; Kilicman, Adem (Springer Open, 2011)
The purpose of this paper is to introduce two novel subclasses Γλ(n, α, β) and Γ∗λ(n, α, β) of meromorphic p-valent functions by using the linear operator Dnλ. Then we prove the necessary and sufficient conditions for a function f in order to be in the new classes. Further we study several important properties such as coefficients inequalities, inclusion properties, the growth and distortion theorems, the radii of meromorphically p-valent starlikeness, convexity, and subordination properties. We also prove that the results are sharp for a certain subclass of functions.